2010
DOI: 10.1016/j.otohns.2010.06.116
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and Quality of Life in Patients on Voice Rest

Abstract: and associated lesions. 2) Provide pre-and postoperative data on perceptive, acoustic and aerodynamic voice parameters. METHOD: We retrospectively reviewed the charts of patients treated in our department between 1998 and 2008 for sulcus vocalis and related lesions using the CO2-laser assisted endoscopic surgery with digital scanning, based on the technique described by Cornut and Bouchayer, and intraoperative collagen injection when vocal atrophy was present. Epidemiological data, perceptive, acoustic and aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A meaningful study of voice rest would necessitate compliance with recommended parameters during that period of time. Rousseau et al have described relatively low self‐reported “complete compliance” of 35% among patients who were prescribed voice rest . An additional 44% reported that they “almost never” used their voice.…”
Section: Introductionmentioning
confidence: 99%
“…A meaningful study of voice rest would necessitate compliance with recommended parameters during that period of time. Rousseau et al have described relatively low self‐reported “complete compliance” of 35% among patients who were prescribed voice rest . An additional 44% reported that they “almost never” used their voice.…”
Section: Introductionmentioning
confidence: 99%